2019
DOI: 10.3389/fonc.2019.01213
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Acquired Radioresistance Induction Between Repeated Photon and Particle Irradiation

Abstract: In recent years, advanced radiation therapy techniques, including stereotactic body radiotherapy and carbon–ion radiotherapy, have progressed to such an extent that certain types of cancer can be treated with radiotherapy alone. The therapeutic outcomes are particularly promising for early stage lung cancer, with results matching those of surgical resection. Nevertheless, patients may still experience local tumor recurrence, which might be exacerbated by the acquisition of radioresistance after primary radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…Several different irradiation (IR) schedules with or without chemotherapy are presently explored in the clinical practice of NSCLC therapy. In many cases of tumor recurrence after primary radiotherapy, patients can rarely be treated again with the same radiation regimen because the tumor might acquire radioresistance [28]. The proposed processes contributing to enhanced cellular tolerance to MFR included cell cycle checkpoint responses and activation of pro-survival signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several different irradiation (IR) schedules with or without chemotherapy are presently explored in the clinical practice of NSCLC therapy. In many cases of tumor recurrence after primary radiotherapy, patients can rarely be treated again with the same radiation regimen because the tumor might acquire radioresistance [28]. The proposed processes contributing to enhanced cellular tolerance to MFR included cell cycle checkpoint responses and activation of pro-survival signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, repopulation of tumors and regeneration of normal tissue are critical in the success of fractionated RT. The relationship between the 4Rs of RT and radioresistance acquisition has been summarized recently by Sato et al [ 174 ].…”
Section: Radiocurability and Radiation Therapy Resistancementioning
confidence: 99%
“…Some authors have suggested that the accumulation of DNA damage by repeated X-ray irradiation favors both EMT and CSCs enrichment, which increase oncogenic activity. Secondary induction of a CSC subpopulation by EMT also contributes to the induction of radioresistance [ 174 ]. The differences between photon and particle irradiation concerning the effects of repeated in vivo irradiation remain largely unknown.…”
Section: Future Perspectives In Radiation Oncology Targeting Cscs:mentioning
confidence: 99%
“…Although antitumor immunity is induced by radiotherapy, the effect may be limited due to the presence of radioresistant suppressor cell types in the tumor microenvironment. [ 62 ] In addition, tumor irradiation induces the expression of immune checkpoint molecules, such as PD‐L1, and upregulates TGF‐β signaling, which triggers a wound healing response. This process may facilitate tumor recurrence.…”
Section: Radiotherapy and Its Immunomodulatory Effectmentioning
confidence: 99%